Mobile Networks and Management First International Conference, MONAMI 2009, Athens, Greece, October 13-14, 2009. Revised Selected Papers - Pentikousis, Kostas; Blume, Oliver; Agüero, Ramon; Papavassiliou, Symeon (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2010)
The First International ICST Conference on Mobile Networks and Management (MONAMI) was held in Athens, Greece during October 13-14, 2009, hosted by the National Technical University of Athens. Through what we hope will be a long-lasting series of events, this new international conference aims at bringing together top - searchers, academics, and practitioners specializing in the area of mobile network management. Multiaccess and resource management, mobility management, and n- work management have emerged as core topics in the design, deployment, and ope- tion of current and future networks. Yet, they are treated as separate, isolated domains with very little interaction between the experts in these fields and lack cro- pollination. MONAMI 2009 offered the opportunity to leading researchers, industry professionals, and academics to meet and discuss the latest advances in these areas and present results related to technologies for true plug-and-play networking, efficient use of all infrastructure investments, and access competition. MONAMI 2009 featured eight full papers and five short papers, which were - lected after a thorough peer-review process based on their relevance to the scope of the conference and their technical merit. The overall acceptance rate was 50%. The contributing authors covered a range of topics in mobile networks and their mana- ment that are currently of high interest in the wireless research area.